Sur le chemin de l’école : perceptions de parents et d’enfants du primaire face au risque routier lors de la mise en place d’un Trottibus au Québec - Sylvanie Godillon (Enfances, Familles, Générations, 2018)
Research Framework: In Western countries, the rate of children walking to school has been in steady decline since the late 1990s. This reduction has changed the relationship that children have with public spaces. To counter this decline, walking school bus programs such as Trottibus have been implemented to encourage children to walk to school. This program works in a similar manner to a bus route, but instead of taking a bus, children walk to school accompanied by adults who act as the “bus drivers”, supervising them on their way to school. Objectives: These programs have been evaluated in the past, but little research has focused on differentiating the perceptions of parents and children. The objective of this article is to analyze the differences in perceptions of road risk between parents and children at the beginning of their involvement in Trottibus, the walking schoolbus program funded by the Canadian Cancer Society (CSC-Québec). Methodology: Our methodology relied on a web-based, self-administered survey conducted with 189 parents and their children aged 5 to 11 years before their participation in the Trottibus program (or at the very beginning of the program). Results: The results showed a greater sense of safety for children when walking in a pedestrian-friendly space and a greater confidence in other road users’ respect for pedestrians. According to parents, the Trottibus has educational benefits in terms of pedestrian mobility. Children and parents highlighted the social aspects of this program as being an outstanding. Conclusions: The results provide a better understanding of children's familiarity with school travel and their perceptions of road safety under various scenarios (walking on the sidewalk, crossing the street, playing on the street, etc.) as well as documenting differences between the expectations of parents and children. Contribution: The accompaniment of children by adults questions how exploring the city (through the journey to school) can help children to become more independent. If parents are afraid to let their child walk from home to school alone at ages where independent mobility is experienced, children might not acquire the skills required to travel safely and experience public spaces in cities.